The Role of Islam in the Abolition of Slavery and in the Development of British Capitalism (American Journal of Islam and Society, 2012)
West Indian scholars have overlooked the role played by the Muslim leadership in West Africa in bringing an end to the transatlantic trade in Africans. The jihād movements in West Africa in the late eighteenth century gave political unity to West Africa challenging the collaboration of European trade in Africans with the pagan slave traders. West Indian historiography, while emphasizing European abolitionist movements, ignores the Islamic unity (tawhīd) of humankind, which brought together many ethnically heterogeneous enslaved African Muslims to successfully challenge the West Indian plantation system. The exploitation of the human resources and the immense wealth of the then Moghul India and Imperial China by British colonialism helped develop the British industrial capitalism, which controlled most of the world until the end of World War II. The security of the British industrial capitalist complex could no longer depend on the small-scale West Indian plantation economies but on the large-scale economies of Asia protected by the British imperial forces under the British imperial flag.